Two‐Dimensional Multicomponent Quasicrystal as Bifunctional Electrocatalysts for Alkaline Oxygen and Hydrogen Evolution Reactions - Mishra, Shashank Shekhar; Kumbhakar, Partha; Nellaiappan, Subramanian; Katiyar, Nirmal Kumar; Tromer, Raphael; Woellner, Cristiano F.; Galvao, Douglas S.; Tiwary, Chandra S.; Ghosh, Chanchal; Dasgupta, Arup; Biswas, Krishanu (Energy technology (Weinheim, Germany), 2023)
The presence of weak interlayer interactions and in‐plane covalent character in quasicrystals facilitate the synthesis of the two‐dimensional multicomponent alloy by chemical exfoliation. The first large‐scale formation of atomically thin 2D sheets by chemical exfoliation from the multicomponent Al70Co10Fe5Ni10Cu5 decagonal quasicrystalline alloy is reported. The exfoliated ultrathin two‐dimensional multicomponent alloy exhibits an excellent oxygen evolution reaction/hydrogen evolution reaction bifunctional catalytic activity in alkaline electrolyte, i.e., alkaline water splitting. The active surface area of the 2D sheets also provides a large number of active sites for the bifunctional catalysis of the oxygen and hydrogen evolution reactions. These 2D atomically thin sheets exhibit superior catalytic performance to their bulk counterparts. Molecular dynamics and density functional theory simulations of the 2D alloy support the experimental interpretation in terms of structural stability and catalytic properties. Synthesis of this type of new class 2D material provides a promising approach for the design and exploration of nonprecious transition metal‐based electrocatalysts toward clean energy production. The article presents a design of multicomponent alloy with a decagonal quasicrystal phase with low‐cost transition metals (Al70Co10Fe5Ni10Cu5) and elucidates the exfoliating of metallic alloy into a two‐dimensional thin sheet. 2D surfaces are unique, like many metal atoms exposed on the surface act as a bifunctional catalyst. This is promising as an alternative to noble metal catalyst materials.